Systematic review and meta-analysis of small bowel dose–volume and acute toxicity in conventionally-fractionated rectal cancer radiotherapy. (September 2019) - Holyoake, Daniel L.P.; Partridge, Mike; Hawkins, Maria A.
Highlights: Acute GI toxicity is highly prevalent and dose-limiting in the treatment of rectal cancer. The dose–volume relationship for the small bowel is inadequately understood. We have conducted meta-analysis of published dose–volume-histogram datasets. We found a significant increase in toxicity with increased irradiated volume. We also showed increased risk with increased dose for a given irradiated volume. Abstract: Introduction: The limited radiation tolerance of the small-bowel causes toxicity for patients receiving conventionally-fractionated radiotherapy for rectal cancer. Safe radiotherapy dose-escalation will require a better understanding of such toxicity. We conducted a systematic review and meta-analysis using published datasets of small bowel dose–volume and outcomes to analyse the relationship with acute toxicity. Materials and methods: SCOPUS, EMBASE & MEDLINE were searched to identify twelve publications reporting small-bowel dose–volumes and toxicity data or analysis. Where suitable data were available (mean absolute volume with parametric error measures), fixed-effects inverse-variance meta-analysis was used to compare cohorts of patients according to Grade ≥3 toxicity. For other data, non-parametric examinations of irradiated small-bowel dose–volume and incidence of toxicity were conducted, and a univariate logistic regression model was fitted. Results: On fixed-effects meta-analysis of three studies (203 patients), each of the dose–volume measures V5Gy –V40Gy were significantly greater ( p  < 0.00001) for patients with Grade ≥3 toxicity than for those without. Absolute difference was largest for the lowest dose–volume parameter; however relative difference increases with increasing dose. On logistic regression multiple small-bowel DVH parameters were predictive of toxicity risk (V5Gy, V10Gy, V30Gy – V45Gy ), with V10Gy the strongest ( p  = 0.004). Conclusions: Analysis of published clinical cohort dose–volume data provides evidence for a significant dose–volume-toxicity response effect for a wide range of clinically-relevant doses in the treatment of rectal cancer. Both low dose and high dose are shown to predict toxicity risk, which has important implications for radiotherapy planning and consideration of dose escalation for these patients.